Pengaruh Stres Kerja Terhadap Kepuasan Kerja karyawan Universitas Andalas Dalam Rangka Menerapkan Pengelolaan Keuangan Badan Layanan Umum (BLU) - Siska, Adilla Juita (Jurnal Ekonomi, 2011)
This study aims to obtain empirical evidence of the influence of job satisfaction of employees Andalas University in order to implement the financial management Public Service Board (BLU). To perform the testing stages of data used 284 employees at the Ueversity Andalas Padang. The process of data collection is done by using the observation that involved researchers directly. The research data used are the primary data that sought to spread the research questionnaire to the respondent who has met ihe criteria of sampling. Within this study there are two types ofvariables used, thefirst is a variable that is independent of job stress. Second is the dependent variable isjob satisfaction. The process of hypothesis testing is done by quantitative methods. The model used is linier regression. Based on test results found that job stress had no significant effect on job satisfaction of employees Andalas University in order to implement the financial management of Public Service Board (BLU).